Roman Catholic Pastoral Theology An Adolescent Ministry Scholar's Perspective - Canales, Arthur David (2018)
The article demonstrates a need and placement of Roman Catholic pastoral theology and serves to offer important revelations about the state of pastoral theology in the Catholic tradition. The overarching goal of this article is to address several components of Catholic pastoral theology: its distinctive nature, the many theological and ministerial areas within its discipline, its scope and purpose, its themes and issues, its prospective future, and finally, reflections on my experience as an adolescent ministry scholar. The article attempts to deepen the conversation of Catholic pastoral theology and to highlight some of its strengths and growing edges.
Keywords: Catholic; Formation; Ministry; Pastoral; Theology